ANALISIS PENERAPAN PSAK NO. 45 PADA YAYASAN MASJID AL FALAH SURABAYA - Rizky, Diyani Ade (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
Considering the demand of accountability and transparency in the public sector as well as the importance of financial report which is arranged by non-profit organization, therefore the in depth discussion about the financial report which refers to the PSAK no.45, it is necessary to analyze it more deeper. The object of this research is the foundation of Surabaya Al Falah Mosque. The purpose of this research is to find out the arrangement, the form and the content of financial report of the foundation which refers to the provisions of PSAK no.45. The result of the research indicates that: (1) The foundation have not the guidelines of organization structure yet which is divide the authority and responsibility. (2) The financial report is presented in appropriate with PSAK no.45, but there is some of account that have not been presented in accordance with PSAK no. 45 which is the classification of net asset. (3) The recognition of uncollectible account receivable was recognized directly.Keywords : PSAK no.45, Non-Profit Organization, Financial Report